Human Rights Due Diligence: Risks of modern slavery for workers displaced by conflict - Savill, Eloise; Hoff, Suzanne (Anti-Trafficking Review, 2024)
This short paper outlines some of the risks of exploitation that people fleeing conflict-affected areas face when trying to access employment in countries of transit and destination. It argues that businesses have a responsibility to prevent and mitigate these risks in their operations and supply chains. Based on interviews with civil society representatives in six European countries, this paper provides a list of measures that employers can take to protect their employees from exploitation.